2018
DOI: 10.1002/jcb.27142
|View full text |Cite
|
Sign up to set email alerts
|

MFG‐E8/integrin β3 signaling contributes to airway inflammation response and airway remodeling in an ovalbumin‐induced murine model of asthma

Abstract: Asthma is the most common chronic childhood disease worldwide, characterized by airway remodeling and chronic inflammation, orchestrated primarily by Th2 cytokines. The aim of the current study was to explore the influences of milk fat globule epidermal growth factor 8 (MFG-E8)/integrin β3 signaling involved in airway inflammation and remodeling in asthma. BALB/c mice were sensitized by intraperitoneal injection of ovalbumin (OVA), followed by OVA nebulization. The levels of MFG-E8 expression were declined mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Increasing infiltration of leukocytes around the airway, particularly eosinophils, is one of the main factors in the pathogenesis of asthma ( 36 ). The present study demonstrated that DEX effectively decreased inflammatory cell infiltration in the airway and inhibited mucus overproduction in OVA-induced asthmatic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing infiltration of leukocytes around the airway, particularly eosinophils, is one of the main factors in the pathogenesis of asthma ( 36 ). The present study demonstrated that DEX effectively decreased inflammatory cell infiltration in the airway and inhibited mucus overproduction in OVA-induced asthmatic mice.…”
Section: Discussionmentioning
confidence: 99%
“… 68 , 69 Conversely, interactions between Mfge8 and integrin β3 subunits protect against allergen induced airway remodeling changes, including goblet cell hyperplasia. 70 …”
Section: Epithelial Changes In Airway Remodelingmentioning
confidence: 99%
“…Thus, β3 may serve as a putative therapeutic target in ameliorating sepsis (Chen et al, 2020). In an ovalbumin-induced asthma murine model, administration of recombinant milk fat globule epidermal growth factor 8 (MFG-E8) suppressed both lung inflammation and airway remodeling by binding with its receptor integrin β3 (Zhi et al, 2018). It has been shown that integrin αMβ2 is essential for the adherence of neutrophils to endothelial cells as well as for transmigration (Hahm et al, 2013).…”
Section: Integrins In Health and Disease I: Inflammationmentioning
confidence: 99%